Cost-Sharing and Use of Health Services in Italy: Evidence from a Fuzzy Regression Discontinuity Design - Michela Ponzo; Vincenzo Scoppa (Institute for the Study of Labor (IZA), 2016)
We use a Regression Discontinuity Design (RDD) to evaluate the impact of cost-sharing on the use of health services. In the Italian health system, individuals reaching age 65 and earning low incomes are given total exemption from cost-sharing for health services consumption. Since the probability of exemption changes discontinuously at age 65, we use a Fuzzy RDD in which the age threshold is used as an instrument for exemption. We find that prescription drug consumption, specialist visits and diagnostic checks remarkably increase with exemption. However, using several measures of health outcomes we do not find any change in individual health.
Keywords: I10; I13; I11; I18; C26; 330; health insurance; healthcare demand; cost-sharing; moral hazard; health outcomes; fuzzy regression discontinuity design; instrumental variables